GROWING STUDENTS' LEARNING ACTIVITY THROUGH ICT-BASED SIMULATION MODEL ON ONLINE LEARNING IN ELEMENTARY SCHOOL - Velayati, Mei Akbar; Prastowo, Andi (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract This study aimed to describe how learning through ICT-based simulation model in online learning affected the learning activities of students in elementary schools. This study was descriptive qualitative research using a case study method conducted at Pelita Cemerlang Elementary School, Pontianak. Data collection used two data sources, namely primary data obtained from interviews and observations and secondary data obtained from books, journals or relevant scientific articles through e-books and e-journals. Data analysis was carried out by reducing the data, presenting the data and drawing conclusions. The research results indicated that implementing ICT-based simulation model in online learning fostered students’ learning activities. It proved by each indicator of learning activities, namely: the involvement of students in completing the assigned tasks, actively asking questions, being involved in discussions, being able to solve the problems given, being active in finding information related to the material provided, and able to assess their abilities.